2015
DOI: 10.1159/000442088
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism and Presenteeism among Care Workers in Swiss Nursing Homes and Their Association with Psychosocial Work Environment: A Multi-Site Cross-Sectional Study

Abstract: Background: Worker productivity is central to the success of organizations such as healthcare institutions. However, both absenteeism and presenteeism impair that productivity. While various hospital studies have examined the prevalence of presenteeism and absenteeism and its associated factors among care workers, evidence from nursing home settings is scarce. Objective: To explore care workers' self-reported absenteeism and presenteeism in relation to nursing homes' psychosocial work environment factors. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 35 publications
1
28
0
5
Order By: Relevance
“…The study showed that presenteeism was most common among care assistants and that its prevalence among nursing professionals did not deviate from that among the all other occupations group. The high prevalence of presenteeism found among care assistants is in line with findings from studies from other countries [3][4][5][6]11,20,[27][28][29]. Unlike the present study, other studies have found that nursing professionals have higher levels of presenteeism than other occupations [7,9,16,17,30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study showed that presenteeism was most common among care assistants and that its prevalence among nursing professionals did not deviate from that among the all other occupations group. The high prevalence of presenteeism found among care assistants is in line with findings from studies from other countries [3][4][5][6]11,20,[27][28][29]. Unlike the present study, other studies have found that nursing professionals have higher levels of presenteeism than other occupations [7,9,16,17,30].…”
Section: Discussionsupporting
confidence: 90%
“…Sickness presenteeism, attending work while ill, has increased during the last few decades [1,2], especially among nurses and care assistants [3][4][5] and other healthcare employees [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses and care assistants have been found to have an increased risk of presenteeism as well as relatively high sick leave rates, a finding that they have in common with other health care employees . The most commonly given reason for presenteeism among nurses in Sweden as well as among other health care employees was “not wanting to increase the burden for colleagues” (57% and 52% respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Findings on the role of peer and supervisor support have been mixed, with some quantitative studies indicating a negative association with presenteeism [9,10] and others failing to identify a relationship. [11] Mixed findings have also been demonstrated in relationship to teamwork [12,13] and job insecurity. [14,15] Much of this research has used quantitative research methods and, with a few exceptions [6] has been a-theoretical.…”
Section: Introductionmentioning
confidence: 99%
“…[7] And finally, in Swiss healthcare workers, quantitative findings demonstrated that low staffing levels were linked to higher levels of presenteeism and supportive leadership was related to a lower likelihood of such behaviour. [13] There have been few qualitative explorations of presenteeism in healthcare settings. These would allow an in-depth investigation into individuals' experience of presenteeism, and their explanations about why they choose to attend, rather than not to attend, work when unwell.…”
Section: Introductionmentioning
confidence: 99%